ANALISIS BUDAYA KONSUMTIF RUNNING GEARS PADA ANGGOTA KOMUNITAS LARI DI SULAWESI SELATAN - Muhammad - Harliawan; Akbar Sudirman; Ihsan Abbas (Universitas Negeri Padang, 2023)
Based on the research results obtained, and after analyzing the data, members of the running community in South Sulawesi put forward the principle of the use of goods in consumptive running gears. In addition to the principle of utility in consumptive running gears, members of the running community in South Sulawesi are also used as motivation or support so that they can be more consistent for running, running gears are also used as a style by members of the running community in South Sulawesi, both in the community and when participating in Fun Run events. This research uses a case study approach. case study is a model that emphasizes the exploration of a system that is limited to a case or several cases in detail, accompanied by in-depth data mining involving various sources of information that are rich in context. Through this approach, it is expected to be able to describe the motivation to join the running community and the consumption of running equipment by the running community in South Sulawesi. The findings of this study generally show that running gears have a very significant effect on members of the running community in South Sulawesi